P PENGEMBANGAN PEDOMAN PELAKSANAAN HEALING CLASS BERBASIS KEARIFAN LOKAL BALI MELALUI PENGINTEGRASIANNYA KE DALAM PROGRAM GERAKAN DISIPLIN SISWA (GDS) DI SMA NEGERI 3 MENGWI - Nurvenayanti, Intan; Kertih, I Wayan; Maryati, Tuty (Ganesha Civic Education Journal, 2025)
This study aims to develop, validate, and examine the effectiveness of the Healing Class Guideline Book based on Balinese local wisdom integrated into the Student Discipline Movement (GDS) Program at SMA Negeri 3 Mengwi, focusing on improving students’ discipline and cooperation. The study applied the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects consisted of four expert validators, and data were collected through interviews, observations, questionnaires, and documentation, analyzed using descriptive quantitative and qualitative methods. The results show that: (1) The developed guideline consists of five chapters emphasizing musyawarah (sangkepan)-based reflective learning; (2) validity testing indicated a valid category with an average score of 75% (range 72.60–89.42); and (3) the program’s implementation achieved 75% positive responses in improving discipline and cooperation behaviors. Therefore, the Healing Class Guideline based on Balinese local wisdom integrated into GDS is suitable as a cultural-based character education reference in senior high schools.